The Alliance for Progress in Uruguay: Political Dynamics, Legacy and Lessons Learned - Garcé, Adolfo (Journal of Leadership, Accountability and Ethics, 2021)
During the first half of the 1960s, under the auspices of the Alliance for Progress, Uruguay carried out the most ambitious planning effort of its history. The government set up an office to design the plans: the Technical Secretariat of the Commission on Investment and Economic Development (CIDE, in Spanish). In late 1965, the CIDE made available to the government its most important product, the National Economic and Social Development Plan (1965-1974). In early 1966, the government formally approved the plan, but never implemented it. However, both economic and social information and reform proposals generated by CIDE deeply permeated the political debate and the positions of the main social and political actors. This experience confirms the main conclusions of the research and policy “nexus” literature but, at the same time, invites us to devise and put forward new hypotheses.